Undercover Economist strikers back: how to run- or ruin- an economy - Harford, Tim (London, 2013)
A million readers bought The Undercover Economist to get the lowdown on how economics works on a small scale, in our everyday lives. Since then, economics has become big news. Crises, austerity, riots, bonuses - all are in the headlines all the time. But how does this large-scale economic world really work? What would happen if we cancelled everyone's debt? How do you create a job? Will the BRIC countries take over the world? Asking - among many other things -- what the future holds for the Euro, why the banks are still paying record bonuses and where government borrowing will take us, in The Undercover Economist Strikes Back, Tim Harford returns with his trademark clarity and wit to explain what's really going on - and what it means for us all.
Keywords: Macroeconomics